Analisis Kebutuhan Bahan Ajar Berbasis Case Methode pada Mata Kuliah Sejarah Sosial Ekonomi - Lestari, Nur Indah; Aprilia Triaristina; Myristica Imanita (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to determine the need for case-based teaching materials in the Socio-Economic History course. This study uses a descriptive qualitative method. This study uses a descriptive qualitative method by describing the research data obtained from the teaching materials needs analysis questionnaire. The subjects in this study were students of the History Education Study Program, FKIP, University of Lampung with a total of 80 students as respondents. The results of the study indicate that the analysis of teaching materials needs indicates that students need teaching materials for Socio-Economic History arranged with the following criteria: 1) arranged systematically, 2) easy to understand and clear language, 3) containing real case examples relevant to socio-economic conditions, and 4) equipped with visualizations (graphs, tables, maps and infographics) of the material arranged accompanied by images, charts, or visual data. The method used in the Socio-Economic History textbook is based on the case method. In conclusion, case-based learning encourages students to be active in conveying critical ideas related to various issues and enables students to understand the relationship between historical events and the socio-economic dynamics of society in a more in-depth and contextual manner. Keywords: Case Method; Social Economic His, Teaching Materials.